"Downhill" Esophageal Varices due to Dialysis Catheter-Induced Superior Vena Caval Occlusion: A Rare Cause of Upper Gastrointestinal Bleeding. (20th February 2013) - Nayudu, Suresh Kumar; Dev, Anil; Kanneganti, Kalyan
Abstract : "Downhill" varices are a rare cause of acute upper gastrointestinal bleeding. Rarely these varices are reported in patients receiving hemodialysis as a complication of chronic dialysis vascular access. We present a case of acute upper gastrointestinal bleeding in an individual with end-stage renal disease receiving hemodialysis. Esophagogastroduodenoscopy revealed "downhill" varices in the upper third of the esophagus without any active bleeding at the time of the procedure. An angiogram was performed disclosing superior vena caval occlusion, which was treated with balloon angioplasty. Gastroenterologists should have a high index of suspicion for these rare "downhill" varices when dealing with acute upper gastrointestinal bleeding in patients receiving hemodialysis and manage it appropriately using endoscopic, radiological, and surgical interventions.